Yoga Intervention in the Aftermath of an Earthquake in Iceland. The Effect of Six-week Hatha Yoga Program on Psychological Complications following an Earthquake. - Kolbrún Þórðardóttir 1950- (2010)
Background: The strain of responding to stressful situations can be cumulatively detrimental over time and lead to physical and mental disorders. Many research indicate that positive coping strategies as yoga are one kind of self-helping mind-body relaxation technique that works to enhance stress-coping mechanisms. Few studies have explored the effect of hatha yoga practice on stress and stress related symptoms in the aftermath of a natural disaster. Design: This was a non-randomized, community intervention with pre- and post-intervention valid measurements. Objective: To evaluate the effectiveness of hatha yoga on perceived stress and stress related symptoms. Participants: Fifty eight individuals, from highly exposed earthquake areas were self selected into the research and divided into an experimental group and a control group on a waitlist. Intervention: A hatha yoga program emphasizing balance of physical activity, breathing exercises and mindfulness meditation was instructed twice a week for six weeks. Several questionnaires were administered and blood pressure measured pre- and post intervention. Results: Multivariate analysis of variance (MANOVA) showed statistically significant improvement of quality of relations (P<.035) and quality of sleep (P<.029) measured by subscales of IQL. Participants in both groups showed a significant improvement in concentration, well being and quality of life. There was a significant improvement in stress, post-trauma symptoms, depression and anxiety from pre to post intervention in both groups. Conclusion: Current findings suggest that hatha yoga may be considered as a valuable self-helping strategy to improve sleep and relations. Studies of a long-term hatha yoga practice on PTSD and moderate to high levels of anxiety and depression are suggested. Research on the use of hatha yoga as an intervention in early stage of traumatic situation and crisis is recommended. Keywords: Anxiety, Concentration, Depression, Natural disaster, Sleep, Stress, Yoga Rannsókn þessi var ...